REDESIGN OF CICAHEUM BUS TERMINAL BANDUNG - Raksa Maulana Subki (Sean Institute, 2022)
Terminal is a transportation infrastructure and is part of a road network system to multiply the transportation system for passenger and freight transportation. Regional development cannot be separated from a process to advance the community in an area, which is carried out systematically through a process of planning, designing, and evaluating. In the TOD that will be planned, the Bandung City Government will renovate the Cicaheum terminal which is no longer feasible because it does not provide easy access for passengers, lack of parking space, poor terminal security and comfort as well as unclear space restrictions between vehicles and users resulting in increased vulnerability to crime, lack of supporting facilities such as waiting rooms become a serious problem because waiting passengers spill or staying in the area of the bus vehicle. theme in the design of the Cicaheum terminal of motion efficiency. In the concept of the terminal is a utility architecture. As well as the style used is modern.The area of the location also affects the supporting factors in the terminal. Cicaheum Terminal which is regulated in the Bandung City Regional Regulation and the bandung city Wilayang Spatial Plan rules, in 2011-2031 the area of the terminal for cicaheum itself is inadequate so it requires expansion and design that is made to prioritize the rules of the game in government regulations. The government plans to change the cicaheum terminal for the better.